Derivação de uma escala de tempo de Descorrelação Lagrangiana para uma Camada Limite Estável - Moreira, Virnei Silva; Degrazia, Gervásio Annes; Roberti, Débora Regina; Maldaner, Silvana (Ciência e Natura, 2013)
In the present study a new formulation for the lagrangian decorrelation time scale in the stable boundary layer (CBL) is proposed. This new model is compared with a well-known relation proposed by Sorbjan (1989).